PORTARIA SE/PRMA Nº 127, DE 13 DE OUTUBRO DE 2016 - Flavio Roberto Martins de Matos (DMPFe de 02/06/2016, n. 89, Administrativo, p. 44, 2016)
Altera a composição da fiscalização do Contrato nº 08/2014 relativo à construção do prédio sede da PRM/Caxias